Enhanced Closed Incisional Negative Pressure Therapy for Treating Infectious Scars - Xingran Liu, MD; Qiumei Ji, MD; Jing Yang, MD; Qingfeng Li, MD, PhD; Kai Liu, MD, PhD; Ru-Lin Huang, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Chronic infectious pathological scars, characterized by mutual reinforcement between infection and pathological scarring, pose challenges in reconstructive surgery. We introduce an enhanced closed incisional negative pressure therapy following a 1-stage surgery to simultaneously eradicate infection and alleviate wound tension. Methods:. A total of 25 patients who underwent chronic infectious pathological scar treatment by using this enhanced closed incisional negative pressure therapy were retrospectively reviewed. The outcomes were evaluated by postoperative recurrence frequency of infection and scarring during a 1-year follow-up, as well as the Patient and Observer Scar Assessment Scale and quality-of-life scores. Results:. After treatment, no serious complications, such as incision dehiscence, occurred. The average wound healing time was 12.68 days. Only 1 patient experienced surgical site scarring. Besides, average infection frequency decreased significantly from 6.40 to 0.00 times per year (P < 0.0001). The Patient and Observer Scar Assessment Scale score decreased from 81.60 to 25.36 (P < 0.0001), whereas the quality-of-life score increased from 2.20 to 4.88 (P < 0.0001). Conclusions:. The enhanced closed incisional negative pressure therapy effectively facilitated infectious wound healing in a 1-stage operation and simultaneously prevented infection and scarring recurrence in long-term follow-up, resulting in satisfactory postoperative outcomes.